Raman spectroscopy: Incorporating the chemical dimension into dermatological diagnosis - Amit Sharma; Shruti Sharma; Anna Zarrow; Robert A Schwartz; W Clark Lambert (Wolters Kluwer Medknow Publications, 2016)
Raman spectroscopy provides chemical analysis of tissue in vivo. By measuring the inelastic interactions of light with matter, Raman spectroscopy can determine the chemical composition of a sample. Diseases that are visually difficult to visually distinguish can be delineated based on differences in chemical composition of the affected tissue. Raman spectroscopy has successfully found spectroscopic signatures for skin cancers and differentiated those of benign skin growths. With current and on-going advances in optics and computing, inexpensive and effective Raman systems may soon be available for clinical use. Raman spectroscopy provides direct analyses of skin lesions, thereby improving both disease diagnosis and management.